Institutional Gaps and Halal Opportunities: Assessing Bulgaria’s Readiness for Cold Chain Agro-Exports to MENA - Petrov , Daniel (Unisia, 2025)
This study examines Bulgaria’s institutional, infrastructural, and market readiness to develop specialized cold-chain logistics for agri-food exports to the MENA and Eurasian regions. Applying a qualitative methodology grounded in documentary analysis and SWOT evaluation, the research integrates national policy documents, legislative frameworks, and international indices to assess the coherence between agricultural production potential and logistical capabilities. Findings reveal a clear asymmetry between Bulgaria’s strong agroecological base and its limited institutional capacity to manage temperature-sensitive and certified exports. The absence of a unified national authority for certification, traceability, and cold-chain governance results in fragmented responsibilities and inefficiencies across ministries. Although Bulgaria benefits from favorable geography, access to EU funding, and inclusion in trans-European corridors, infrastructural specialization for perishable goods remains underdeveloped. The SWOT analysis identifies governance fragmentation and lack of refrigerated terminals as critical weaknesses, while opportunities arise from expanding halal markets and EU green logistics initiatives. The results confirm the hypothesis that institutional and infrastructural integration—rather than productive capacity—is the key determinant of Bulgaria’s export competitiveness. The study concludes that creating a national cold-chain and certification framework, aligned with EU and international standards, could reposition Bulgaria as a strategic logistics hub linking European production to dynamic MENA and Eurasian food markets.